Modelling the regional economic impacts of road pricing in an interregional general equilibrium framework - Chris Jensen-Butler; Bjarne Madsen (European Regional Science Association (ERSA), 2001)
In Denmark in recent years there has been a substantial debate both popular and academic concerning the consequences of introducing road pricing - both the regional consequences and whether road pricing gives a double dividend by reducing environmental externalities and by financing a tax reform where the incentive to work is increased through reduction in income tax rates. In this paper, the discussion on road pricing in Denmark is summarised: In the last 10 years, tax reforms have moved the tax burden to environmental taxation and away from income taxation. The argument has been the "double dividend", where environmental tax reforms both induce environmental improvements and provide welfare gains from a reduction in income tax rates increasing labour supply and production. Lately, the existence of a double dividend has been questioned and it has been argued that only environmental reforms reducing the relative welfare from leisure time activities and increasing the benefits from working will give a double dividend. Next the distributional problems from road pricing are discussed. The point of departure is different road pricing schemes, which have been proposed in Denmark and the discussion of double dividend, where road pricing can be used to change the relative prices between working and leisure time activities. Finally, an applied interregional general equilibrium model for Danish municipalities, LINE is presented. The first results from the calculation with the model are presented and methods to model the double dividend are presented.
Keywords: 330